Interim Compensation Scheme - Ministry of Information and Broadcasting (Ministry of Information and Broadcasting, 1954)
Over six years have elapsed since Partition, when 1,000,000 families (5,000,000 persons) were forced to migrate from West Pakistan to India. The story of how this mass of uprooted humanity is being resettled in this country has often been told, but may here bear brief repetition.
Ministry of Information and Broadcasting
Ministry of Information and Broadcasting